FROUDE NUMBER VARIANCE WITH RESPECT TO THE HYDRODYNAMIC RESPONSE OF A NON-STATIC VEHICLE AT A LOW-LYING FLOODED ROADWAY - Shah, Syed Muzzamil Hussain; Mustaffa, Zahiraniza; Khahro, Shabir Hussain; Yusof, Khamaruzaman Wan; Ab Ghani, Aminuddin; Al-qadami, Ebrahim Hamid Hussein; Teo, Fang Yenn (IIUM Engineering Journal, 2020)
In terms of stability, the response of static cars in floodwaters has been widely investigated. However, the hydrodynamics of a non-static vehicle exposed to such events are less explored. Herein the study ponders the assessment of the hydrodynamic forces experienced by a non-static vehicle attempting to cross a low-lying flooded street. With that regards, a Perodua Viva was modeled (1:10) and tested in the Hydraulics Laboratory under partial submergence and sub-critical flows, fulfilling the similarity laws. Since the Froude number could best analyze the flow conditions, the behavior of the hydrodynamic forces and the Froude number have been the focus of this investigation. From the study of outcomes, an inverse relation of the Froude number with respect to the buoyancy force, along with positive trends relating to drag, frictional, and rolling resistance, were noticed. ABSTRAK: Dari segi kestabilan, tindak balas kereta statik dalam air banjir telah banyak dikaji. Walau bagaimanapun, hidrodinamik kenderaan tidak statik yang terdedah kepada kejadian seperti itu kurang diterokai. Kajian ini menilai daya hidrodinamik kenderaan tidak statik yang cuba melintas jalan raya yang banjir. Sehubungan itu, sebuah Perodua Viva dimodelkan (1:10) dan diuji dalam Makmal Hidraulik di bawah perendaman separa dan didedahkan kepada aliran sub-kritikal, seperti ketika kejadian. Manakala nombor Froude adalah terbaik dalam menganalisa keadaan aliran air. Oleh itu, tindak balas daya hidrodinamik dan nombor Froude menjadi fokus penyelidikan ini. Dapatan kajian menunjukkan kaitan terbalik nombor Froude pada daya apungan, sedangkan tren positif yang berkaitan dengan daya tarik, geseran dan rintangan guling diperhatikan.